Coopting the State: The Conservative Evangelical Movement and State-Level Institutionalization, Passage, and Diffusion of Faith-Based Initiatives - Rebecca Sager; Keith Bentele (Religions, 2016)
In the following, we characterize the contemporary conservative Evangelical movement as an example of contentious politics, a movement that relies on both institutional and noninstitutional tactics to achieve political outcomes. Examining multiple institutional and legislative outcomes related to the Faith Based Initiative, we seek to understand why some states have established state faith-based bureaucracies and passed significantly more faith-based legislation. We find that the influence of elite movement actors within state Republican parties has been central to these policy achievements. Furthermore, we find that the presence of movement-inspired offices increase the rate of adoption of legislation, and the passage of symbolic policies increases the likelihood of passage of more substantive faith-based legislation. We argue that the examination of multiple outcomes over time is critical to capturing second order policy effects in which new institutions, the diffusion of legislation and institutions, and increasing policy legitimacy may shape subsequent legislative developments.